Rare isolated pancreatic myeloid sarcoma in a pediatric patient - A case study with literature review - Somayah Alsolami; Bayan Hafiz; Abeer Mehdar; Hatim Almaghraby (Elsevier, 2022)
Myeloid sarcoma (MS) is an extramedullary hematopoietic tumor of immature myeloid cells. It is more common in males, and may present across a wide range of age groups. It rarely occurs in isolation and is chiefly associated with AML, of which it may be the first presentation. Most patients with MS will progress to AML within one year of diagnosis, but this can be delayed with early detection and treatment. Isolated MS is very rare, but can occur at any site in the body. MS in the pancreas is uncommon and can simulate the symptoms of pancreatitis or adenocarcinoma, making this a challenging diagnosis. Here, we present a case of MS diagnosed in a 12-year-old boy with no known history of AML. To our knowledge, this is the first reported case of isolated pancreatic myeloid sarcoma in Saudi Arabia.